From the Mouths of Monkeys: Detection of Mycobacterium tuberculosis Complex DNA From Buccal Swabs of Synanthropic Macaques - Alicia K. Wilbur (2018)
Although the Mycobacterium tuberculosis complex (MTBC) infects a third of all humans, little is known regarding the prevalence of mycobacterial infection in nonhuman primates (NHP). For more than a century, tuberculosis has been regarded as a serious infectious threat to NHP species. Advances in the detection of MTBC open new possibilities for investigating the effects of this poorly understood pathogen in diverse populations of NHP. Here, we report results of a cross-sectional study using well-described molecular methods to detect a nucleic acid sequence (IS6110) unique to the MTBC. Sample collection was focused on the oral cavity, the presumed route of transmission of MTBC. Buccal swabs were collected from 263 macaques representing 11 species in four Asian countries and Gibraltar. Contexts of contact with humans included free ranging, pets, performing monkeys, zoos, and monkey temples. Following DNA isolation from buccal swabs, the polymerase chain reaction (PCR) amplified IS6110 from 84 (31.9%) of the macaques. In general, prevalence of MTBC DNA was higher among NHP in countries where the World Health Organization reports higher prevalence of humans infected with MTBC. This is the first demonstration of MTBC DNA in the mouths of macaques. Further research is needed to establish the significance of this finding at both the individual and population levels. PCR of buccal samples holds promise as a method to elucidate the mycobacterial landscape among NHP, particularly macaques that thrive in areas of high human MTBC prevalence. © 2012 Wiley Periodicals, Inc.